KADAR N, P DAN K TANAH PADA TANAMAN KELAPA SAWIT MENGHASILKAN DENGAN BERBAGAI KOMPOSISI PENANAMAN TANAMAN SELA DI BAWAH TEGAKAN - Dina Arsyi Fazrin; Chairani Hanum; Irsal Irsal (Universitas Sumatera Utara, 2014)
NPK soil on oil palm produce plantation with increase diversity of vegetation. Soil fertility level onthe oil palm produce will be decreased, because there is no vegetation. Therefore, one the effort toincrease the soil productivity with planting of vegetation diversity under oil palm trees. Theresearch aimed to know NPK soil on oil palm produce plantation with increase diversity ofvegetation. The research was carried out in the PTPN III Kebun Bangun Simalungun regency,North Sumatera from September to Desember 2013. The experiment design was non factorialCompletely Randomized Design with 5 levels intercrop compotition, Arachis glabrata 100%,Stenotaphrum secundatum 100%, Arachis glabrata 50% + Stenotaphrum secundatum 50%, Arachisglabrata 75% + Stenotaphrum secundatum 25% dan Arachis glabrata 25% + Stenotaphrumsecundatum 75%. The analysis of data using the analysis variance and continued by DMRT. Theresults of this research showed that diversity compotitions intercrops given significant effect on thefresh weight leaf of Stenotaphrum secundatum 100%, the dry weight leaf of Stenotaphrumsecundatum 100%, the fresh weight root of Arachis glabrata 75%, the dry weight root of Arachisglabrata 75% and could increased the levels of soil phosphorus, but not significant effect on the oilpalm leaf chlorophyll, the intercrops leaf chlorophyll, the levels of soil nitrogen and potassium.Keywords: Intercrops, NPK soil, leaf chlorophyll